Analisis Tingkat Kesehatan Bank dengan Menggunakan Metode Camel Pada Perbankan BUMN yang Terdaftar di Bursa Efek Indonesia - Iman Indrafana KH (Journal of Management and Economics Research, 2022)
Banks are financial institutions that very important role in economic activity. Face competition in the banking sector are more stringent, the trust of the public is one of the keys to success that drives the progress of banking. To be morer trusted by the public in the financial management of the business, interest will be measuring the health of banks needs to be done by the bank. One source that can be used is to analyze the financial statements of the bank. This research is purposed to analyze the rating performance condition of BUMN banks by using CAMEL and also to know differences in the health between banks BUMN the periode 2016-2020. Analysis tool used is the CAR, KAP, NPM, ROA, BOPO, dan LDR. The study population was all the banks listed on the Stock Exchange. The sample used BUMN bank BNI, BRI, BTN, and Bank Mandiri. Data used published financial statements of the bank in 2016-2020. The result showed not all banks BUMN for 2016-2020 are predicate healthy because just banks BNI, BRI and Mandiri predicate healthy while bank BTN predicate healthy enough. The result also shows there are differences in the health of banks in the fourth BUMN bank for five years with a NPM ratio, but on the ROA and LDR ratios only BTN bank has different in the health of bank with the other three bank BUMN